'An ambitious club on a small scale': the rise of the Royal Isle of Wight Golf Club 1882–1914. Issue 4 (1st October 2016) - Wheeler, Paul
ABSTRACT: In this article, the notable, but forgotten, history of the Royal Isle of Wight Golf Club (RIWGC), founded in 1882, is used to examine the cultural and social shifts that enabled the development of the sport's popularity across late Victorian and Edwardian society in Britain. The club can justifiably be described as notable because for a brief period this small island club was at the centre of developments which helped shape golf during this era and framed its development in the twentieth century. Two archetypally entrepreneurial Victorian gentlemen, Captain Jack Eaton and Charles John Jacobs, were central to the club's success and their endeavours underpinned the club's illustrious status. This paper examines newspaper records, periodicals and local archives to explain how the RIWGC originated and then prospered in tandem with the development of the Isle of Wight as an upmarket holiday destination. Moreover the article shows how the club provided access for both sexes of the English upper middle class to a sport and an environment that delivered the cultural benefits and the social kudos which could be derived from association with a golf club, and particularly one that was one of a select group of 'Royal' golf clubs. However, research also demonstrates that the club provided an environment where enterprising and talented men from less privileged backgrounds could seize the opportunity to become famous on the national and even the international stage. Finally it will demonstrate that the RIWGC had a significant role in codifying the rules of golf in the 1880s when the R&A appeared hesitant to take the lead.